Year in Review 2018 - Breast Cancer Edition - Amorim, Gilberto Luiz da Silva; Gagliato, Debora; Guimaraes, Andrea Paiva Gadelha; Marta, Gustavo Nader; Morikawa, Lisa; Pimenta, Juliana Martins; Sanches, Solange (Brazilian Journal of Oncology, 2018)
The Breast Cancer community witnessed the presentation of several important studies though 2018. From molecular evaluation of primary breast tissue to predict chemotherapy benefit, to major advances in systemic therapy in the metastatic setting, clinical trials highlighted in this BJO especial edition have truly major impact in current clinical practice for breast cancer patients.
Keywords: Breast Neoplasms; Review; Combined Modality Therapy